Associations between concurrent neonicotinoid, pyrethroid, and organophosphate insecticide metabolites and neurocognitive performance in Ecuadorian adolescents - Jessica Yen; Kun Yang; Tuo Lin; Xin M. Tu; Georgia Kayser; Rajendra P. Parajuli; Ana Skomal; Sheila Gahagan; Jose Suarez-Torres; Suzi Hong; Raeanne C. Moore; Jose R. Suarez-Lopez (Science of The Total Environment, 2025)

Associations Between Urinary Pesticide Metabolites and Serum Inflammatory Biomarkers in Adolescents Living in an Agricultural Region - Mohammed N. Hussari; Briana N. C. Chronister; Kun Yang; Xin Tu; Danilo Martinez; Rajendra P. Parajuli; Jose Suarez-Torres; Dana Boyd Barr; Suzi Hong; Jose R. Suarez-Lopez (Exposure and Health, 2025)

Elucidating the role of peripheral monocyte nicotinic acetylcholine receptors and inflammation in cognitive outcomes in older adults - Jordan N. Kohn; Gavrila Ang; Christopher Pruitt; Isabel Gandarilla; Xin Tu; Suzi Hong (Biogerontology, 2025)
Nicotinic acetylcholine receptors (nAChRs) are important regulators of brain and immune function that play critical roles in the neuropathology and progression of Alzheimer’s disease and related dementias (ADRD). However, quantifying nAChRs in the brain remains elusive, and little is known about peripheral measures of nAChR in older adults or their relationship to cognition. Here, we examined associations between nAChR expression and immunoregulatory function in peripheral blood monocytes and cognitive performance among 167 older adults (age 72.3 ± 7.6 years; 71% female). Penalized linear and logistic regression were used to identify nAChR-related features in classical, intermediate, and nonclassical monocytes, as well as immunophenotypes, clinical and sociodemographic factors, associated with cognitive status (Montreal Cognitive Assessment; MoCA). Intermediate monocytes had the highest expression of alpha-7 nAChRs and greater ex vivo inflammatory responses (83.7% TNF-ɑ + cells) relative to classical (68.4%, d = 1.98, P d = 3.20, P N = 76) had higher soluble CD14 levels (1777 ± 377 pg/uL) and greater anticholinergic medication burden (ACB; mean = 1.76) than normocognitive participants (NC: N = 91; 1638 ± 352 pg/uL sCD14, t 155 = 2.78, P = 0.006; mean ACB: 1.05, t 143 = 3.13, P = 0.002). Multivariate regression models indicated that stronger nAChR-mediated immunoregulation in intermediate monocytes was associated with higher MoCA scores (beta = 0.13) and 14% lower odds of MCI, as well as lower ACB (beta = − 2.10; 95% CI − 4.14, − 0.61). This study demonstrates that peripheral monocytes exhibit subset-specific differences in nAChR phenotypes in older adults and provides preliminary evidence for their association with cognitive function and a potential mediating role between ACB and cognitive impairment.